2020
DOI: 10.1093/mnras/staa189
|View full text |Cite
|
Sign up to set email alerts
|

Distant foreground and the Planck-derived Hubble constant

Abstract: It is possible to reduce the discrepancy between the local measurement of the cosmological parameter H 0 and the value derived from the Planck measurements of the Cosmic Microwave Background (CMB) by considering contamination of the CMB by emission from some medium around distant extragalactic sources, such as extremely cold coarse-grain dust. Though being distant, such a medium would still be in the foreground with respect to the CMB, and, as any other foreground, it would alter the CMB power spectrum. This c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Finally, we consider the possibility that the CMB is contaminated by intergalactic dust, which in turn would affect the H global 0 required by Planck Collaboration VI (2020). Some distant foreground emission can increase H global 0 (Yershov et al 2020), which would slightly reduce the mild tension between our model and the strong lensing data (Figure 7). This is because the z > 0.4 lenses all give H 0 systematically above the Planck prediction by a similar extent.…”
Section: Cmb Contamination By Intergalactic Dustmentioning
confidence: 74%
See 1 more Smart Citation
“…Finally, we consider the possibility that the CMB is contaminated by intergalactic dust, which in turn would affect the H global 0 required by Planck Collaboration VI (2020). Some distant foreground emission can increase H global 0 (Yershov et al 2020), which would slightly reduce the mild tension between our model and the strong lensing data (Figure 7). This is because the z > 0.4 lenses all give H 0 systematically above the Planck prediction by a similar extent.…”
Section: Cmb Contamination By Intergalactic Dustmentioning
confidence: 74%
“…The H 0 values from the four highest redshift lenses of Wong et al (2020) give a median (mean) of 71.3 km s −1 Mpc −1 (70.8 km s −1 Mpc −1 ), which is 3.9 km s −1 Mpc −1 (3.4 km s −1 Mpc −1 ) higher than the Planck prediction. This systematic offset can be reduced if the background H 0 is underestimated due to errors in the Planck measurements caused by intergalactic dust (Yershov et al 2020; see also Vavryčuk 2018Vavryčuk , 2019. We discuss this issue further in Section 5.3.8.…”
Section: Assessing the Tension For Mondmentioning
confidence: 99%
“…It has been suggested that galactic halos contain interstellar dust grain fraction of about 1-3% in mass, and the rest is H 2 , He and other heavier molecules [31,32]. Halo dust grains are expected to be at a slightly higher temperature with respect to that of the gas, about 5 K or so, depending on the cloud position within the galactic halo [33], but as a first approximation, we assume here that dust and gas are at the same temperature, i.e., 2.7 K.…”
Section: Virial Cloud Modelmentioning
confidence: 99%
“…This led to the introduction of dark energy into the standard cosmological model (SCM) [4,5]. However, there is still a wide discussion on cosmological models and their parameter values [6][7][8][9]. The wCDM model, where the ΛCDM model is a special case of one, is often considered an alternative to SCM.…”
Section: Introductionmentioning
confidence: 99%